2012
DOI: 10.1016/j.jcps.2011.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Brands as intentional agents framework: How perceived intentions and ability can map brand perception

Abstract: Building on the Stereotype Content Model, this paper introduces and tests the Brands as Intentional Agents Framework. A growing body of research suggests that consumers have relationships with brands that resemble relations between people. We propose that consumers perceive brands in the same way they perceive people. This approach allows us to explore how social perception theories and processes can predict brand purchase interest and loyalty. Brands as Intentional Agents Framework is based on a well-establis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
519
1
6

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 482 publications
(584 citation statements)
references
References 40 publications
24
519
1
6
Order By: Relevance
“…This space usefully describes a variety of human social perceptions: over US samples, both convenience [students, adults (23)] and representative [adults (24)]; over dozens of countries, using their own social groups (26,27); over time [Italian Fascists (28); American students since 1933 (29)]; over levels of analysis, from individuals (30) to subtypes of women and men (31), immigrants (32), gay men (25), and African Americans (33); and even over other intent-having entities, such as animal species* and corporations (34,35). These warmth-by-competence data suggest the bold conclusion that the dimensions are universally descriptive of group images.…”
Section: Identifying Whom To Trustmentioning
confidence: 99%
“…This space usefully describes a variety of human social perceptions: over US samples, both convenience [students, adults (23)] and representative [adults (24)]; over dozens of countries, using their own social groups (26,27); over time [Italian Fascists (28); American students since 1933 (29)]; over levels of analysis, from individuals (30) to subtypes of women and men (31), immigrants (32), gay men (25), and African Americans (33); and even over other intent-having entities, such as animal species* and corporations (34,35). These warmth-by-competence data suggest the bold conclusion that the dimensions are universally descriptive of group images.…”
Section: Identifying Whom To Trustmentioning
confidence: 99%
“…First, it can be scaled beyond the individual. Since brands are recognized as being intentional agents (Kervyn, Fiske, & Malone, 2012), the DAS²-theory can be applied to those entities as well. These naturally include traditional brand holders, such as commercial brands, but also political entities (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…Eckes (2002), for instance, found that 'businessman' and 'businesswoman' types are perceived as 'envious' , whereas the 'housewife' type is viewed as 'paternalistic' . They have also been shown to apply to consumer context (Kervyn, Fiske, & Malone, 2012;Zawisza & Pittard, 2015).…”
Section: Theorizing Stereotypes: Moving Towards the Stereotype Contenmentioning
confidence: 99%